2014
DOI: 10.1002/btpr.1880
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical monitoring as applied to clean‐in‐place (CIP) and steam‐in‐place (SIP) operations in biopharmaceutical manufacturing

Abstract: Multivariate statistical process monitoring (MSPM) is becoming increasingly utilized to further enhance process monitoring in the biopharmaceutical industry. MSPM can play a critical role when there are many measurements and these measurements are highly correlated, as is typical for many biopharmaceutical operations. Specifically, for processes such as cleaning-in-place (CIP) and steaming-in-place (SIP, also known as sterilization-in-place), control systems typically oversee the execution of the cycles, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, the variable-wise unfolding does not require such estimation, making it applicable for online monitoring. 9,18,19 Wold et al 20 concluded that the former was oriented to evaluating the completed batch as normal or abnormal, while the latter focused more on the monitoring of individual time points. 20 The primary objective of this study was to identify the occurrence of an anomalous event online.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, the variable-wise unfolding does not require such estimation, making it applicable for online monitoring. 9,18,19 Wold et al 20 concluded that the former was oriented to evaluating the completed batch as normal or abnormal, while the latter focused more on the monitoring of individual time points. 20 The primary objective of this study was to identify the occurrence of an anomalous event online.…”
Section: Methodsmentioning
confidence: 99%
“…Two commonly used indexes to detect anomalies or faults are the Q-statistic 18 and the Hotelling's T 2 statistic. 9,23 The Q-statistic is computed as the squared sum of residuals: 8…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations